Species Specific DNA Damage Induced by Hexavalent Chromium in Three Major Carps: Effect of Hexavalent Chromium on DNA of Carps - Fariha Latif; Muhammad Naeem; Sana Aziz; Rehana Iqbal; Safina Kousar; Faiza Ambreen (Biological Sciences - PJSIR, 2024)
Among xenobiotics, metals gained attention because of their toxicity and harmful effects on aquatic ecosystems, fish and human health. Present research work focused on the toxicological effects of hexavalent chromium on the DNA of three major carps viz. Cirrhina mrigala, Labeo rohita and Catla catla by using the comet assay. All three fish species were exposed to four sub-lethal concentrations (213rd, 113rd, 114th and 115th of LC50) of chromium for six exposure durations (14, 28, 42, 56, 70 and 84 days). All three fish species exhibited significantly variable exposure dose and time dependent DNA damage in terms of damaged nuclei, GDI and CTL in their erythrocytes. Among the fish species, C. mrigala showed maximum DNA damage with the highest damaged nuclei (44.28±25.97%), GDI (1.52±0.84) and CTL (126.91±75.71 µm), whereas significantly lower DNA damage was observed in C. catla. At various exposure durations, DNA damage was observed to be significantly higher at 56 days of exposure which then reduced afterward, however, at various exposure concentrations of chromium, maximum DNA damage was observed at 213rd of LC50 of metal followed by 113rd, 114th and 115th of acute toxicity of chromium for all three fish species under study.